Motivasi Memoderasi, Kompetensi dan Etos Kerja terhadap Prestasi Kerja PT Sapta Sentosa Jaya Abadi Muko-Muko - Ana Marfuah; Kusuma Chandra Kirana; Didik Subiyanto (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2022)
This research aims to determine the effect of competence and work ethic on work performance with motivation as a moderating variable. In this study using a population of all employees of PT. Sapta Sentosa Jaya Abadi Muko-Muko with a total of 70 respondents, the sampling technique used saturated sampling with questionnaires which were distributed to all employees of PT. Sapta Sentosa Jaya Abadi Muko-Muko. This research is a quantitative research. Data analysis techniques used in this research are descriptive analysis, multiple regression analysis, and Moderate Regression Analysis (MRA). The results of this study indicate that the competence variable has a positive and significant effect on work performance, the work ethic variable has a positive and significant effect on work performance, the motivation variable has a positive and significant effect on work performance, the motivation variable can moderate competence on work performance, The motivation variable cannot moderate work ethic on work performance Keywords: Motivation, Competence, Work Ethic, Work Performance